The rise and fall of Christian civilization in the modern world - Strehle, Stephen, 1952- author. aut Link Link Link
1 online resource.
Keywords: "In this compelling narrative, discover how Christianity-particularly through Puritanism-shaped the foundations of modern Western democracy, only to see its influence dramatically transformed by the forces of secularization. This accessible yet profound work The Rise and Fall of Christian Civilization in the Modern World traces two pivotal movements that defined our modern world: the rise of Puritan ideals that birthed concepts of liberty, equality, and democracy, and the subsequent emergence of secular society that challenged religious authority. From the democratic principles of early Puritan churches to the development of social contract theory, from revolutionary movements to the rise of the secular state, this book illuminates how religious and anti-religious forces shaped our current cultural landscape. The author masterfully weaves together historical events, theological developments, and philosophical shifts that transformed Western civilization-from the Protestant Reformation to the French Revolution, from the Enlightenment to the modern entertainment industry. Written in clear, engaging prose and organized in concise chapters perfect for discussion groups and classrooms, this work offers both general readers and scholars a comprehensive understanding of how Christianity's cultural influence evolved from a dominant force to one voice among many in our contemporary pluralistic society. More than a historical account, it provides crucial insights into the ongoing dialogue between faith and secularism in modern life"-- Provided by publisher.